Scientific Opinion on the substantiation of health claims related to a combination of Lactobacillus fermentum 57A, Lactobacillus plantarum 57B and Lactobacillus gasseri 57C and defence against vaginal pathogens (ID 934, further assessment) pursuant to Article 13(1) of Regulation (EC) No 1924/2006 - EFSA Panel on Dietetic Products, Nutrition and Allergies (NDA) (EFSA Journal)
Abstract Following a request from the European Commission, the Panel on Dietetic Products, Nutrition and Allergies was asked to provide a scientific opinion on a health claim pursuant to Article 13 of Regulation (EC) No 1924/2006 in the framework of further assessment related to a combination of Lactobacillus fermentum 57A, Lactobacillus plantarum 57B and Lactobacillus gasseri 57C and defence against vaginal pathogens. The food constituent that is the subject of the claim, a combination of Lactobacillus fermentum 57A, Lactobacillus plantarum 57B and Lactobacillus gasseri 57C, is sufficiently characterised. The claimed effect, defence against vaginal pathogens, is a beneficial physiological effect. The target population is the female population. No human intervention studies were provided from which conclusions could be drawn for the scientific substantiation of the claim. On the basis of the data presented, the Panel concludes that a cause and effect relationship has not been established between the consumption of Lactobacillus fermentum 57A, Lactobacillus plantarum 57B and Lactobacillus gasseri 57C and defence against vaginal pathogens.